2004
DOI: 10.1007/s10517-004-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of regulation of erythropoiesis during hemolytic anemia

Abstract: We studied changes in the erythroid hemopoietic stem during phenylhydrazine-induced hemolytic anemia. Stimulation of erythropoiesis was associated with increased functional activity of erythroid precursors, which resulted from changes in feeder capacity of hemopoiesis-inducing microenvironmental cells and erythropoietic activity of the plasma. The development of encephalopathy induced by a hemolytic poison was accompanied by a decrease in hyperplasia of bone marrow erythropoiesis. It was related to a decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Our previous studies demonstrated that the development of encephalopathy is accompanied by disadaptation of the erythron system (erythropoietic distress) [5,6,10,11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies demonstrated that the development of encephalopathy is accompanied by disadaptation of the erythron system (erythropoietic distress) [5,6,10,11].…”
Section: Resultsmentioning
confidence: 99%
“…These changes are manifested in a decrease in hyperplasia of the erythroid hemopoietic stem due to reduction of committed precursor count in the bone marrow and formation of abnormal erythrocytes [5,6,10,11]. Hyperactivation of the sympathoadrenal system during the posthypoxic period is associated with decompensation of the inhibitory transmitter mechanisms highly sensitive to oxygen deficiency [1,3,13].…”
mentioning
confidence: 99%
“…Phenylhydrazine-induced haemolytic condition causes stimulation of erythropoiesis which is associated with increased functional activity of erythroid precursors and resulting in changes in the regulatory capacity of a haemopoietic milieu of the plasma. 51 Thus, the increase in corticosterone level may possibly be due to the stimulation of erythropoiesis primarily in human bone marrow progenitor cells. Our findings indicate that HEASR combined with DXM has a distinct functional effect and may have therapeutic benefit in combination.…”
Section: Discussionmentioning
confidence: 99%